Impact of patient selection in clinical trials: application of ROCKET AF and ARISTOTLE criteria in GARFIELD-AF - Himmelreich, Jelle C L; Virdone, Saverio; Camm, John; Pieper, Karen; Harskamp, Ralf E; Oto, Ali; Jacobson, Barry F; Sawhney, J P S; Lim, Toon Wei; Gibbs, Harry; Goto, Shinya; Haas, Sylvia; et al. (Open heart, 2024)
BACKGROUND: The extent to which differences in results from Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE) and Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial (ROCKET) atrial fibrillation (AF)-the landmark trials for the approval of apixaban and rivaroxaban, respectively, for non-valvular AF-were influenced by differences in their protocols is debated. The potential influence of selection criteria on trial results was assessed by emulating these trials in data from the Global Anticoagulant Registry in the Field (GARFIELD)-AF registry. METHODS: Vitamin K antagonist (VKA) and non-vitamin K oral antagonist (NOAC) users from GARFIELD-AF were selected according to eligibility for the original ARISTOTLE or ROCKET AF trials. A propensity score overlap weighted Cox model was used to emulate trial randomisation between treatment groups. Adjusted HRs for stroke or systemic embolism (SE) within 2 years of enrolment were calculated for each NOAC versus VKA. RESULTS: Among patients on apixaban, rivaroxaban and VKA, 2570, 3560 and 8005 were eligible for ARISTOTLE, respectively, and 1612, 2005 and 4368, respectively, for ROCKET AF. When selecting for ARISTOTLE criteria, apixaban users had significantly lower stroke/SE risk versus VKA (HR 0.57; 95% CI 0.34 to 0.94) while no reduction was observed with rivaroxaban (HR 0.98; 95% CI 0.68 to 1.40). When selecting for ROCKET AF criteria, safety and efficacy versus VKA were similar across the NOACs. CONCLUSION: Apixaban and rivaroxaban showed similar results versus VKA in high-risk patients selected according to ROCKET AF criteria, whereas differences emerged when selecting for the more inclusive ARISTOTLE criteria. Our results highlight the importance of trial selection criteria in interpreting trial results and underline the problems faced in comparing treatments across rather than within clinical trials.
Keywords: Risk Assessment; Pyrazoles; Anticoagulants; Pharmacology, Clinical; Randomized Controlled Trials as Topic; výsledek terapie; rizikové faktory; ženské pohlaví; lidé; Pyridones; Patient Selection; inhibitory faktoru Xa; STROKE; Administration, Oral; mužské pohlaví; rivaroxaban; senioři; Stroke; Rivaroxaban; registrace; Registries; aplikace orální; Risk Factors; Treatment Outcome; Aged; Humans; fibrilace síní; pyridony; výběr pacientů; Factor Xa Inhibitors; vitamin K; Female; hodnocení rizik; antikoagulancia; Atrial Fibrillation; Male; randomizované kontrolované studie jako téma; cévní mozková příhoda; Biostatistics; pyrazoly; Vitamin K